Conception of the social action by M. Weber and its reflection in German communicative philosophy - Lebedeva, Svitlana (Actual Problems of Mind, 2017)
The paper deals with the conception of social action by M. Weber which is a component of his «understanding sociology» and its influence to the development of German communicative philosophy. The author claims that treatment of social action and rationality by Weber underlies the conceptions by K.-O. Apel and J. Habermas and has also influenced indirectly the system theory by N. Luhmann.